Family Involvement In the Lives of the Elderly In the Working Area of the Lapadde Health Center, Pare - Pare City - Tawil, Muh. Risal; Anto, Sardi; Treasa, Adisty Dwi; Susanti, Susi; Hamzah, Abd Natsir; Fadli, Khalikul (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
As the number of elderly increases, there are many problems experienced by the elderly, including not being educated, not having access to health care, not having old age security, not having social support from family or friends to care for them. Life changes in the elderly cause various problems, including dependence on other people, health problems and poverty. Reduced ability to respond to stress, repeated losses and physical changes place elderly people at risk of disease and functional disorders. In general, elderly people experience limitations, so that the quality of life of the elderly decreases. The aim of this research is to determine the relationship between the role of the family and the quality of life of the elderly in the Lapadde Community Health Center working area. This research method is quantitative research using a cross sectional method taken using a purposive sampling technique. The chi square test results obtained a value of ρ = 0.000 (ρ < α = 0.05). This means that there is a relationship between the role of the family and the quality of life of the elderly in the Posyandu for the Elderly in the working area of the Lapadde Community Health Center . The conclusion is that there is a relationship between the role of the family in the quality of life of the elderly in the Posyandu for the Elderly in the work area of the Lapadde Community Health Center. It is recommended that families maintain good support for the elderly to maintain their quality of life by exercising regularly.